Moving forward: scaling-up the integration of an HIV and hypertension program in Akwa Ibom State, Nigeria - Shivani Mishra; Angela A. Aifah; Daniel Henry; Nina Uzoigwe; Ememobong Bassey Udoh; Esther Idang; Jahnavi Munagala; Deborah Onakomaiya; Nafesa Kanneh; Anyiekere Ekanem; Eno Angela Attah; Gbenga Ogedegbe; et al. (BMC, 2024)
Abstract As people living with HIV experience increased life expectancy, there is a growing concern about the burden of comorbid non-communicable diseases, particularly hypertension. This brief describes the current policy landscape on the management of HIV and hypertension in Akwa Ibom State, Nigeria, stakeholder engagement meetings, and the resulting five policy recommendations rooted in an ongoing research study designed to integrate hypertension management into HIV care across primary health centers in the State. In order to identify the current gaps in integrated care, discussion sessions with three stakeholder groups (i.e., healthcare providers, patient advocacy groups, and policy makers) were held separately in November 2022. The discussions were purposed to brainstorm policy-level solutions for integrating hypertension into HIV treatment. After all the sessions were concluded, there were five recommendations provided by the stakeholders for integrating HIV and hypertension care in the Akwa Ibom State. Stakeholders unanimously agreed with the need to integrate hypertension care for HIV impacted communities in the State. Specifically, stakeholders recommended to: (1) engage retired community health nurses as mentors; (2) actively link communities to integrated care in clinics; (3) integrate hypertension management with HIV education; (4) expand health insurance accessibility; and (5) formally integrate hypertension management into primary healthcare centers in Akwa Ibom State.